Text Space in Contemporary Saudi poetry - Hakami, Majid Dosari (Arts for Linguistic & Literary Studies, 2024)
This study aims to explore the impact of text space and emphasize key writing and typographical methods in Saudi poetic expression. The research is structured into an introduction, a preface, three main sections, and a conclusion. The initial section delves into the significance of text arrangement, focusing on aspects of blank space and text density. The subsequent section examines techniques employed in constructing poetic lines, while the third section analyzes the role of punctuation marks. Findings reveal that contemporary Saudi poetry heavily utilizes text space manipulation to enhance visual communication, fostering diverse interpretations and enriching thematic depth. Additionally, contemporary poets in Saudi Arabia experiment with form and content transformations, utilizing innovative techniques to modernize poetic expression and elevate its artistic and semantic dimensions. This study underscores the emergence of a novel visual writing paradigm among Saudi poets, enabling them to articulate aesthetic and emotional sensibilities in a distinctive manner. Through an examination of poetry collections, it becomes evident how visual elements synergize with textual meaning, hinting at a departure from conventional literary conventions towards a more pictorial linguistic trend.